"It's not about the passport" : the perception of Finnish citizens with a foreign background in the wake of the Refugee Crisis - Sievert, Annika (2017)
This study examines whether the perception of Finnish citizens with a foreign background has changed in the wake of the refugee crisis. To analyse the situation, focus groups with a total of 18 participants with both Finnish citizenship and a foreign background were conducted to establish whether they felt the treatment towards them had changed over the last years. Berry’s model of acculturation and the Interactive Acculturation Model by Bourhis et al. were used to analyse the results and explain acculturation strategies and orientations. The study resulted in two key findings: Finnish citizens with a migration background felt that the perception towards them had changed, but this did not impact their acculturation strategies. Furthermore, most participants felt at home in Finland, but also felt like they were not accepted as Finns by the larger society. These findings indicate that while majority members influence acculturation strategies, they are less likely to impact them after some form of long-term adaptation has been achieved.